Museums as Centers for Education and Research in Teaching History: A Case Study of the Buea Public Museum, Cameroon, 1975–2023 - Wihbongale, Louis Aghogah; Eyong, Ayuk Kingsley (Indonesian Center for Religion and Society Studies (InTReSt), 2025)
This paper examines the role of the Buea Public Museum as a center for education and research in teaching history in Cameroon. Created to bridge the past, present, and future, the museum preserves regional and national artefacts. This includes wooden statuettes, clay pots, calabashes, baskets, and smelting tools that embody the memories and histories of Cameroonian societies. This paper argues that the museum functions similarly to educational institutions such as schools and universities by offering teachers, students, and researchers’ opportunities to engage with tangible heritage and deepen their understanding of local and national history. A qualitative approach was employed, using both primary and secondary data sources. Primary data included observations and interviews with museum curators and personnel, students, educators, and researchers, while secondary sources were complemented by primary evidence to address information gaps. Data were analysed thematically and descriptively. Findings reveal that educators and researchers rarely utilize the Buea Public Museum for teaching and learning purposes, despite its rich didactic potential. This article fills the research gap by examining how museum functions intersect with history education and research within the timeframe of this study. The paper concludes that integrating museum resources into formal education could enhance historical understanding and recommends that teachers and researchers prioritize museums as essential centers for history education and research in Cameroon.